Boundary structure modification and magnetic properties enhancement of Nd–Fe–B sintered magnets by diffusing (PrDy)–Cu alloy. (May 2016) - Tang, Minghui; Bao, Xiaoqian; Lu, Kechao; Sun, Lu; Li, Jiheng; Gao, Xuexu
Abstract: The grain boundary diffusion process was applied to the commercial sintered Nd–Fe–B magnets using Pr68 Cu32, Dy70 Cu30 and Pr35 Dy35 Cu30 ribbons as direct diffusion source. The coercivities increased from 1114.4 kA/m for the original magnet to 1642.8 kA/m for the processed magnet by Pr68 Cu32, higher than 1402.7 kA/m by Dy70 Cu30 . Microstructural investigations showed that the evident coercivity enhancement for the sample by Pr68 Cu32 was mainly attributed to continuous intergranular layers isolating Nd2 Fe14 B grains. Nevertheless, the coercivity enhancement of the sample by Dy70 Cu30 was mainly resulted from the magnetic strengthening of the extensive layers in Nd2 Fe14 B grains.